Comparison of time‐matched aerobic, resistance or combined exercise training in women living with obesity: The EXOFFIT study - Mary E. Davis; Catherine Blake; Gráinne O'Donoghue (Wiley, 2024)
Abstract Background Improvements in cardiorespiratory fitness (CRF) have been shown to largely attenuate the negative health risks associated with obesity. To date, literature on women with obesity has focused upon the evaluation of aerobic‐based exercise interventions. Hence, there is a need to evaluate resistance and combined interventions with this cohort. Objective This study aimed to evaluate the feasibility and efficacy of three exercise modalities in women with obesity for improving CRF, strength, body composition and other health outcomes. Methods Sixty‐seven women with obesity were randomly assigned to the control (CON) or one of three exercise groups (aerobic [AE], resistance [RE], COM). Exercise groups were trained x3 times/week for 12 weeks (up to 150‐min/week). Feasibility outcomes included adherence, attendance, recruitment and retention rates and adverse events. Secondary outcomes were CRF (predicted VO2 max), body composition (body weight [BW], waist circumference [WC], body fat percentage [%BF], fat mass [FM] and lean mass) and strength (5RM bench press, leg dynamometry, grip strength) and self‐reported measures of physical activity, mood, sleep, pain and quality of life. Results Findings support the feasibility of all three exercise modalities in terms of adherence, attendance, and retention. Interventions with a resistance component (COM and RE) were associated with the greatest improvements across the broad range of health outcomes measured. Combined was the most promising for body composition outcomes including body mass index (Effect size [ES] = 0.79, p = 0.04), BW (ES = 0.75, p = 0.05), %BF (ES = 0.77, p = 0.04), FM (ES = 0.83, p = 0.03) and WC (ES = 0.90, p = 0.02), physical activity (i.e., moderate physical activity [ES = 0.69, p = 0.07), mood (ES = 0.83, p = 0.03) and sleep (ES = 0.78, p = 0.04). Resistance was most promising for CRF (ES = 1.47, p = 0.002), strength (i.e., bench press [ES = 2.88, p=<0.001]) and pain (i.e., pain severity [ES = 0.40, p = 0.31]). Conclusions For health outcomes, these results indicate the importance of including a resistance component when prescribing exercise for women with obesity to achieve meaningful improvements. CLINICAL TRIAL REGISTRATION ISRCTN13517067